Komparasi Penerimaan Pajak Hotel, Pajak Restoran Dan Pajak Hiburan Sebelum Dan Setelah Adanya Pandemi Covid-19 - Amalia Dwi Agustina; Arisona Ahmad (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
This research is intended to compare the receipts of Hotel Taxes, Restaurant Taxes, and Entertainment Taxes at the Mojokerto Regency before and during the Covid-19 pandemic. This research uses a quantitative method by testing secondary data sources in the form of Receipts Realization Reports on Hotel Taxes, Restaurant Taxes, and Entertainment Taxes in Mojokerto Regency for the 2018–2021 period with saturated sampling. Data are processed using Paired Sample T-tests with the Statistical Product and Service Solution (SPSS) program. This research proves that the first hypothesis, with the alleged significant difference in Hotel Tax receipts before and during the Covid-19 pandemic in Mojokerto, can be accepted. Then, the second hypothesis with the allegation that the significant difference in Restaurant Tax receipts before and during the Covid-19 pandemic in Mojokerto Regency is not acceptable, And the third hypothesis is that the alleged significant difference in Entertainment Tax receipts before and during the Covid-19 pandemic in Mojokerto Regency can be accepted.